KOMUNIKASI INTERAKSI SIMBOLIK RELAWAN PENDEKAR MENGAJAR DENGAN ANAK DIDIK DI DESA CISADON - Oktaviana Saputri (2021)
The Pendekar Mengajar Community is a forum for Indonesian youths who have a focus on the world of education to teach pre-school or elementary school level children in villages with the aim of serving, shaping character, and encouraging the enthusiasm of children in the village who want or are currently following education in order to achieve goals. The purpose of this study was to see the process of symbolic interaction and the meaning of symbolic interactions in the teaching warrior community. The theory that underlies this research is symbolic interaction according to Herbert Blummer. This study used interviews with five volunteers and two students who were selected by the purposive method. From this research, the results show that the interactions that are built through interpersonal relationships, both formally and informally, are based on each child. There is an exchange of symbols through verbal and nonverbal messages that form meaning during learning. The meaning that is formed from the results of collective action cannot be separated from the three main points of thought in symbolic interactions, namely actions, things and meanings that occur during the learning process.